2014
DOI: 10.2147/ott.s68854
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of the long non-coding RNA PVT1 in human gastric cancer

Abstract: BackgroundHighly sensitive markers are urgently needed for the diagnosis and grading of gastric cancer and for managing drug resistance. The recent identification of long-non-coding RNAs (lncRNAs) has provided new approaches for resolving this challenge. The aim of this study was to screen and identify new biomarkers for human gastric cancer from lncRNAs.MethodsFirst, we used lncRNA microarrays to conduct a preliminary screening for candidate lncRNAs of gastric cancer biomarkers in both human gastric cancer ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 20 publications
5
93
0
Order By: Relevance
“…In addition, overexpression of PVT1 is involved in cancer resistance to chemotherapy. Similar to the results of our previous study, PVT1 was overexpressed in SGC7901 paclitaxel-resistant cells than in untreated SGC7901 cells (14). In the malignant pleural mesothelioma cell, PVT1 knockdown reduced cell proliferation and increased sensitivity to cisplatin (24).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, overexpression of PVT1 is involved in cancer resistance to chemotherapy. Similar to the results of our previous study, PVT1 was overexpressed in SGC7901 paclitaxel-resistant cells than in untreated SGC7901 cells (14). In the malignant pleural mesothelioma cell, PVT1 knockdown reduced cell proliferation and increased sensitivity to cisplatin (24).…”
Section: Discussionsupporting
confidence: 88%
“…To date, overexpression of PVT1 has been frequently observed in several malignant diseases, such as breast cancer, colorectal cancer, ovarian cancer and gastric cancer, and is associated with increasing cell proliferation and inhibiting cell apoptosis (12)(13)(14). Recently, mounting Kanglaite inhibits the expression of drug resistance genes through suppressing PVT1 in cisplatin-resistant gastric cancer cells evidence indicated that PVT1 participated in the drug resistance of cancer cells by regulating different pathways (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen percent to 18% of somatic promoters mapped to noncoding RNAs, including HOTAIR and PVT1, previously associated with gastric cancer (Supplementary Table S3; refs. 52,53). Additional analyses at increasing thresholds of stringency (FC from 1.5 to 2 and FDR from 0.1 to 0.001) yielded similar results, supporting the robustness of this analysis ( Supplementary Fig.…”
Section: Identifying Epigenomic Promoter Alterations In Gastric Cancersupporting
confidence: 74%
“…The ceRNA network we built reveals an unknown ceRNA regulatory network in GC. Recent study also identified that lncRNA interactions with miRNA and mRNA might act as potential diagnosis and prognosis biomarkers in cancer, such as H19, PVT1, HOTAIR, UCA1 and TINCR (7,(48)(49)(50)(51). In our ceRNA network, we also found these key lncRNAs.…”
Section: Discussionsupporting
confidence: 57%